PENERAPAN PELAYANAN PRIMA UNTUK MEMENUHI HARAPAN MASYARAKAT TERHADAP LAYANAN PUBLIK PADA KELURAHAN MAKASAR, JAKARTA TIMUR - Agtovia Frimayasa (Universitas Bina Sarana Informatika, 2017)
This study aims to determine the excellent service (Service Excellent), to meet the expectations of society to public service in the village of Makasar East Jakarta, the results of the study in accordance with procedures and meet the standards that have been applied by governments in almost all kelurahan. This is evident from the work culture applied in this village, as well as adequate facilities and supporting facilities.